THE LAUNDERING OF CRIMINAL CAPITAL AS A THREAT TO THE SECURITY OF RUSSIA'S ECONOMY - S. Chernov (Вестник университета)
In the article there are presented arguments justifying the need for strengthening of fight against legalization of «dirty» money. There are modern interpretation of the laundering of criminal capital. Reviewed and systematized the methods of Bank control. Discusses the functions of the state on countering the legalization of criminal capital is done. Proven link between money laundering and the deterioration of Russia's economic security.